2020
DOI: 10.1590/1519-6984.218195
|View full text |Cite
|
Sign up to set email alerts
|

Root-knot nematode, Meloidogyne javanica, in response to soil fertilization

Abstract: Root-knot nematodes (RKNs) (Meloidogyne spp.) are well known disease problem causing major losses in vegetable crops. Although, chemical nematicides have been used as one of the primary means for controlling RKNs, reliance on these nematicides is associated with heavy costs and negative effects on human health and environment. In this research, the suppressing potential of 6 Iranian commercial fertilizers on RKNs was investigated in laboratory and greenhouse conditions as an alternative to reduce the use of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…The application of vermicompost as organic fertilizer rich in NPK and micronutrients has been reported to significantly suppress plant-parasitic nematodes (Ramakrishnan and Mahadevaswamy, 2011;Hemmati and Saeedizadeh, 2019;Awad-Allah and Khalil, 2019) and as an excellent promoter and protector for crop plants (Chauhan and Singh, 2015). In the present study, vermicompost derived from municipal wastes enhanced plant growth attributes in terms of shoot length (18.5%), total plant fresh weight (32.8%) (Table 4) and significantly reduced (p ≤ 0.05) nematode population ( 64.9%) and root galling (82.5%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The application of vermicompost as organic fertilizer rich in NPK and micronutrients has been reported to significantly suppress plant-parasitic nematodes (Ramakrishnan and Mahadevaswamy, 2011;Hemmati and Saeedizadeh, 2019;Awad-Allah and Khalil, 2019) and as an excellent promoter and protector for crop plants (Chauhan and Singh, 2015). In the present study, vermicompost derived from municipal wastes enhanced plant growth attributes in terms of shoot length (18.5%), total plant fresh weight (32.8%) (Table 4) and significantly reduced (p ≤ 0.05) nematode population ( 64.9%) and root galling (82.5%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the inhibitory toxic effect of different metal nanoparticles (silver nanoparticles, silica oxide nanoparticles, silicon nanoparticles) against M. incognita has been illustrated in several reports [41,42]. In addition, many reports have demonstrated that phosphonate fertilizer (calcium phosphate) has a negative effect on egg hatching and the second-stage juveniles of M. incognita and M. javanica [43,44]. In other authors' work, 4 different fertilizers (NPK, humic acid, agro-health, and azotobarvar-1) were tested for their ability to manage nematode populations in vitro, and the results showed that these fertilizers reduced the egg hatching and increased mortality of the second stage juveniles of root-knot nematodes [45].…”
Section: Discussionmentioning
confidence: 99%
“…Root-knot nematode (RKN) ( Meloidogyne spp.) disease is an important crop disease that has become one of the main factors limiting sustainable crop production ( Gorny et al, 2019 ; Hemmati and Saeedizadeh, 2020 ). RKN infects plant roots and forms nodules, which hinder the absorption of nutrients and water by the roots, leading to wilting and withering; in addition, RKN infection reduces plant resistance, causes wounds, is conducive to infection by other pathogens, and often causes complex diseases ( EFSA Panel on Plant Health et al, 2018 ; Khan and Ahamad, 2020 ), such as Fusarium wilt, root rot, and bacterial diseases ( Khan and Ahamad, 2020 ; Leonetti and Molinari, 2020 ).…”
Section: Introductionmentioning
confidence: 99%